Efficacy and safety data for the XEN45 implant at 2 years: a retrospective analysis. Issue 2 (14th November 2019) - Gabbay, Itay Elimelech; Allen, Felicity; Morley, Christine; Pearsall, Tahmina; Bowes, Oliver Martyn; Ruben, Simon
Abstract : Aim: To report efficacy and safety measures for XEN45 in a National Health Service setting after 24-month follow-up. Methods: This is a retrospective, non-comparative audit of records of patients who underwent XEN45 procedure between June 2015 and May 2017. The main outcome measures were intraocular pressure (IOP) reduction and number of antihypertensive medications at each timepoint. Failure was defined as requiring further surgery or removal of XEN. Success was defined as 20% reduction of IOP without additional glaucoma medications or reduction in antihypertensive medications without increase in baseline IOP. Needling rates were assessed and subgroup analysis was performed. Results: A total of 151 eyes were included in the study. The main diagnoses were primary open angle glaucoma (84.1%), angle closure glaucoma (8.6%) and refractory glaucoma (7.3%). Stand-alone procedure was performed in 62.3% and combined phaco-XEN was done in 37.7%. The mean IOP at baseline was 22.1±6.5 mm Hg, and the mean IOP at 12 and 24 months was 15.4±5.9 mm Hg and 14.5±3.3 mm Hg, respectively (p<0.001). The mean number of medications was 2.77±1.1 at baseline, and 0.3±0.7 and 0.5±1.0 medications at 12 and 24 months, respectively (p<0.001). 25% of patients failed at the 24-month timepoint. Needling was required in 37.7% of patients at 24 months. Non-Caucasian ethnicity was found to be related to higher failure rate. No significant adverse events were noted. Conclusion: XEN45 is a viable, effective and safe procedure after 2 years of follow-up. Patients should be advised regarding failure rate as well as possible need for bleb revisions and medication use.